Influence of Coaching and Capital Loans on Business Development Foster Partners in the Partnership Program (Case Study of PT. Telkom Indonesia's Foster Partners Regional Division IV Semarang) - Farouk, Umar -; Inayah, Inayah -; Shelomita, Ardhia - (Politeknik Negeri Semarang, 2024)
Parts of the essential economy in Indonesia are micro, small, and medium enterprises (MSMEs). Micro, small, and medium enterprises (MSMEs) have a role in overcoming unemployment, poverty, and economic inequality. However, the development of micro, small and medium enterprises as partners of PT Telkom Regional IV partnership program in Semarang in the 2020-2022 period has fluctuated and tends to decline. The aim of this study was to find out the influence of coaching and capital loans on the business development of partners in Semarang. The population in this study amounted to 58 fostered partners. The cencus sample technique was used in this research.. The analysis technique used was descriptive analysis, classical assumption test, and multiple linear regression analysis. The result of this research shows that there is a simultaneous and partial influence between coaching and capital loans on partners”™business development.